Amblyomma ticks in animal carcasses hunted in Mapinguari National Park, Western Amazon, Brazil: New records on species and host-parasite relationships - da Costa, Ivaneide Nunes; Oliveira, Marcela Alvares; de Paulo, Paula Frassinetti Medeiros; Carioca, Angélica Lorena Pereira Mendes; Garcia, Marcos Valério; Aguirre, André de Abreu Rangel; de Medeiros, Jansen Fernandes (Ticks and tick-borne diseases, 2022)
Ticks are obligatory parasites and transmit several pathogens to animals and humans. This study aimed to report the parasitism of ticks on carcasses of animals hunted by hunters from communities near Mapinguari National Park, at the shared border of Amazonas and Rondonia states, northern Brazil. The ticks were collected from heads of carcasses of the following animals: South American tapir (Tapirus terrestris), collared peccary (Pecari tajacu) and long-nosed armadillo (Dasypus beniensis). Six Amblyomma tick species were identified: Amblyomma coelebs, Amblyomma naponense, Amblyomma latepunctatum, Amblyomma oblongoguttatum, Amblyomma scalpturatum, Amblyomma triste and Amblyomma spp. The most abundant tick species were A. oblongoguttatum and A. scalpturatum. DNA extraction and polymerase chain reaction (PCR) were performed on all ticks to test for the presence of rickettsial gltA gene fragments, but no amplification was observed. This study reports, for the first time, the parasitism of A. coelebs in the armadillo D. beniensis and the presence of A. triste in the states of Amazonas and Rondonia, updating the tick fauna to 24 and 39 species for these states, respectively.